MENINGKATKAN PEMAHAMAN BACAAN SISWA SEKOLAH DASAR MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA KOMIK STRIP (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of implementing the Problem Based Learning (PBL) model assisted by comic strip media on elementary school students’ reading comprehension skills. The research employed a pretest–posttest control group design. Class 5A served as the experimental group, while Class 5B served as the control group. Pretest and posttest data were analyzed descriptively to determine improvements in learning outcomes. The results showed that the experimental class experienced a greater increase in scores compared to the control class. The average pretest score of the experimental class was 12.44 and increased to 17.77 in the posttest, while the control class increased from 16.67 to 16.92. These findings indicate that the implementation of PBL assisted by comic strip media is more effective in improving students’ reading comprehension skills than conventional learning.